LATOUR, LE CORBUSIER AND SPIRIT OF THE TIME. - Gogora, Andrej (Sincronía, 2025)
This article investigates late European modernity at the beginning of the twentieth century by examining how the “spirit of the time” (Zeitgeist) is expressed in Le Corbusier’s writings on urbanism, in dialogue with Bruno Latour’s account of modernity. ts main objective is to reassess Latour’s well-known distinction between two modern practices—translation/hybridization and purification—and to argue that purification should not be treated as a purely rational construct. Methodologically, the paper follows a conceptual and hermeneutic approach: it first reconstructs Latour’s thesis on the simultaneous production of hybrids and the ontological separation between humans and non-humans; it then interprets Le Corbusier’s urban discourse as a paradigmatic voice of purification, emphasizing ideals such as objectivity, clarity, strict order, and the conquest of “messy” nature through planning.The analysis highlights a crucial mediating element: the Enlightenment-derived belief in progress, which functions as an emotional and non-rational drive—an enthusiasm or “rage”—that energizes purification and, indirectly, releases hybrid outcomes in the post–World War II city.The paper’s scope is therefore theoretical: it proposes an extension of Latour’s framework by incorporating the affective dimension of progress as a key force shaping modern urbanism and the emergence of complex modern megacities.